UROLOGY RETROPERITONEOSCOPY: INITIAL EXPERIENCE IN CIPTO MANGUNKUSUMO HOSPITAL - Siregar, Ginanda Putra; Wahyudi, Irfan; Mochtar, Chaidir Arif; Hamid, Agus Rizal Ardy Hariandy (Indonesian Journal of Urology, 2016)
Objective: This study was conducted to evaluate the initial experience of retroperitoneoscopy surgery. Material & method: This is a descriptive study with cross-sectional design. Data was collected from medical records of Urology Department in Cipto Mangunkusumo General Hospital Jakarta, from March 2013 until February 2014. Subjects were all patients who performed retroperitoneoscopic surgery between the time periods. Results: Patients consisted of 9 males (42.85%) and 11 females (57.14%). Mean age was 38.95 + 21.88 years old. Proportion based on diagnosis were 5 renal failures (23.8%), 5 ureteral stones (23.8%), 3 renal cysts (14.3%), 2 PUJOs (9.5%), double 3 collecting systems (14.3%), 1 tumor (4.8%), 1 ureteral tumor (4.8%), and 1 renal diverticle (4.8%). Proportion based on kind of retroperitoneoscopy were ureterolithotomy (23.8%), nephrectomy 3 (14.3%), nephroureterectomy 3 (14.3%), renal cyst unroofing 3 (14.3%), heminephrectomy 3 (14.3%), pyeloplasty 2 (9.5%), partial nephrectomy 1 (4.8%), and diverticle coagulation 1 (4.8%). Mean operating time was 178.81 + 55.72 minutes with mean length hospitalization 8.05 + 4.4 days. Mean amount of bleeding was 98 + 69.47 cc, wound operation infection 0 (0%), peritoneal perforation 1 (4.76%), open surgery conversion 2 (9.52%), and transperitoneal laparoscopy conversion 1 (4.76%). Conclusion: In this study, total number of retroperitoneoscopy surgery cases still less than others abroad. Demographic characteristic showed variety than other study. Compared to other studies, the operating time was comparable but the length of stay was longer. We had higher open surgery conversion rate, while another complication was relatively the same.